Spatial attention deficits in humans: the critical role of superior compared to inferior parietal lesions. - Vandenberghe, R; Molenberghs, P; Gillebert, C (2012)
According to a longstanding view, inferior as opposed to superior parietal cortex critically contributes to the spatial attentional deficits encountered following unilateral parietal ischemic lesions. We review the evidence on which this view is based and contrast it with more recent structural lesion evidence concerning the critical role of the intraparietal sulcus in spatial attention deficits. In a classical spatial cueing paradigm, focal lesions of the posterior and of the middle segment of the intraparietal sulcus give rise to a pathological invalidity effect that is indistinguishable from that seen after classical inferior parietal lesions. When a competing distracter is added to a target stimulus, the deleterious consequences of focal IPS lesions are again very similar to those classically observed following inferior parietal lesions. The deficit could not be accounted for by functional effects at a distance affecting inferior parietal cortex. These single-case lesion data establish the critical role of the posterior and the middle IPS segment in spatially selective attention and are in line with a vast amount of functional imaging evidence in the intact brain pointing to the prominent role of the intraparietal sulcus in spatial attention, along with inferior parietal cortex under specific circumstances. Functional imaging has also provided hints about the differences in functional contribution between inferior and superior parietal cortex. These hypotheses await further confirmation based on lesion evidence.